Functional Characterization of the Disease-Associated N-Terminal Complement Factor H Mutation W198R - Cserhalmi, Marcell; Uzonyi, Barbara; Merle, Nicolas S.; Csuka, Dorottya; Meusburger, Edgar; Lhotta, Karl; Prohászka, Zoltán; Józsi, Mihály (Frontiers in Immunology, 2017)
Dysregulation of the complement alternative pathway is involved in the pathogenesis of several diseases, including the kidney diseases atypical hemolytic uremic syndrome (aHUS) and C3 glomerulopathy (C3G). In a patient, initially diagnosed with chronic glomerulonephritis, possibly C3G, and who 6 years later had an episode of aHUS, a heterozygous missense mutation leading to a tryptophan to arginine exchange (W198R) in the factor H (FH) complement control protein (CCP) 3 domain has previously been identified. The aim of this study was to clarify the functional relevance of this mutation. To this end, wild-type (FH1–4WT) and mutant (FH1–4W198R) CCPs 1–4 of FH were expressed as recombinant proteins. The FH1–4W198R mutant showed decreased C3b binding compared with FH1–4WT. FH1–4W198R had reduced cofactor and decay accelerating activity compared with the wild-type protein. Hemolysis assays demonstrated impaired capacity of FH1–4W198R to protect rabbit erythrocytes from human complement-mediated lysis, and also to prevent lysis of sheep erythrocytes in human serum induced by a monoclonal antibody binding in FH CCP5 domain, compared with that of FH1–4WT. Thus, the FH W198R exchange results in impaired complement alternative pathway regulation. The heterozygous nature of this mutation in the index patient may explain the manifestation of two diseases, likely due to different triggers leading to complement dysregulation in plasma or on cell surfaces.